The urgency of developing innovation during the pandemic - Subrata, Sumarno Adi (Universitas Muhammadiyah Magelang, 2021)
The COVID-19 pandemic has changed nearly every aspect of human life, from the individual (how people live, work, and keep their health) to the professional (how healthcare professionals work). Unfortunately, more than three-quarters also approved that the pandemic created significant new opportunities for human growth, although this varies significantly worldwide. Of course, seeing the opportunities developing is not always the same as being able to seize them at times. Fewer than 50 percent of healthcare professionals feel confident that they are prepared to overcome the issues in the COVID-19 era. Most of the human aspect needs health innovation to prevent the long-term outcomes of the pandemic. As expected, they are focusing on maintaining the healthcare system and its continuity, especially in hospital and community settings. Therefore, developing innovation in health, driving productivity and implementing safety measures is needed during the never-ending pandemic. Leaders in the healthcare sector should provide essential strategies supporting innovation-led growth. Keywords: Innovation; pandemic; clinical outcomes; COVID-19; healthcare professionals